2019
DOI: 10.3390/jcm8020215
|View full text |Cite
|
Sign up to set email alerts
|

How the Results of a Randomized Trial of Catheter-Directed Thrombolysis versus Anticoagulation Alone for Submassive Pulmonary Embolism Would Affect Patient and Physician Decision Making: Report of an Online Survey

Abstract: Keywords: pulmonary embolism; submassive; survey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In conclusion, although CDT seems effective on reducing RV load in the acute phase and the bleeding risk is lower compared with ST, evidence regarding its long-term outcomes and effect on mortality is so far absent 30 . Interestingly, a recent survey on clinical decision-making between either CDT or anticoagulation alone in patients with intermediate-risk PE showed that patients are willing to accept a higher risk of bleeding than physicians if it would improve their long-term exercise capacity 31 . This further underlines the importance of studies including assessment of long-term functional outcomes.…”
Section: Catheter-based Therapies In Intermediate-risk Pulmonary Embomentioning
confidence: 99%
“…In conclusion, although CDT seems effective on reducing RV load in the acute phase and the bleeding risk is lower compared with ST, evidence regarding its long-term outcomes and effect on mortality is so far absent 30 . Interestingly, a recent survey on clinical decision-making between either CDT or anticoagulation alone in patients with intermediate-risk PE showed that patients are willing to accept a higher risk of bleeding than physicians if it would improve their long-term exercise capacity 31 . This further underlines the importance of studies including assessment of long-term functional outcomes.…”
Section: Catheter-based Therapies In Intermediate-risk Pulmonary Embomentioning
confidence: 99%